Distinctive gut microbial dysbiosis between chronic alcoholic fatty liver disease and metabolic-associated fatty liver disease in mice - Kang, Kai (Exp Ther Med, 2021)
The gut microbiota, which may affect normal physiological and biochemical functions, has an important role in the development of human liver diseases. The aim of the present study was to investigate differences in the gut microbiota between chronic alcoholic fatty liver disease (AFLD) and metabolic-associated fatty liver disease (MAFLD). AFLD was induced by chronic alcohol administration and MAFLD was induced by a Western-style diet in C57BL/6 mice. After 8 weeks, the levels of plasma alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglyceride (TG), total cholesterol (TC), lipopolysaccharide (LPS), tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β and IL-10 were assessed and H&E staining of mouse liver tissue was performed. High-throughput sequencing of 16S ribosomal DNA from the intestinal contents was used to analyze the different effects of AFLD and MAFLD on the gut microbiota. Differences in the gut microbiota composition were assessed by the t-test. The results revealed increases in LPS, ALT, AST, TG, IL-1β and TNF-α in the AFLD group. Compared with those in the MAFLD control group, the MAFLD group exhibited increased plasma ALT, TG, TC, IL-6, IL-1β and TNF-α levels and decreased plasma IL-10 levels. In addition, the α- and β-diversities revealed that the AFLD and MAFLD groups exhibited obvious changes in the gut structure (with an increase in abundance in the AFLD group and a decrease in abundance in the MAFLD group). In comparison to the AFLD control group, Enterococcaceae were the most abundant bacteria at the family level and Enterococcus and Streptococcus were the most abundant bacteria at the genus level in the AFLD group. However, in the MAFLD group, Lachnospiraceae was the most abundant at the family level, with increases in Erysipelatoclostridium, Gordonibacter and Streptococcus at the genus level and a decrease in the genus Bifidobacterium. In conclusion, the present study confirmed that the AFLD and MAFLD groups harbored differences in the gut microbiota. The marked differences in the gut microbiota at the family and genus levels may contribute to the development process of FLD.